2022
DOI: 10.1038/s41598-022-19238-w
|View full text |Cite
|
Sign up to set email alerts
|

Developing an app-based self-management program for people living with HIV: a randomized controlled pilot study during the COVID-19 pandemic

Abstract: People living with human immunodeficiency virus (PLWH) in Korea demonstrate insufficient self-management behaviors. Especially during pandemics such as COVID-19, technology-based self-management programs are needed to overcome time and space limitations. The purpose of this study was to evaluate the effects of a self-management program using a mobile app (Health Manager) on self-management outcomes among PLWH in Korea. A randomized controlled pilot trial was performed and participants were enrolled in the infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The intervention group used the mobile app for 4 weeks, and the control group received self‐management education materials in a portable document format. The results showed that the app‐based self‐management program was considered a helpful strategy to improve self‐management outcomes among PLHIV and reduce perceived stigma during the pandemic in 33 participants (intervention: n = 17 vs. control: n = 16) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The intervention group used the mobile app for 4 weeks, and the control group received self‐management education materials in a portable document format. The results showed that the app‐based self‐management program was considered a helpful strategy to improve self‐management outcomes among PLHIV and reduce perceived stigma during the pandemic in 33 participants (intervention: n = 17 vs. control: n = 16) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…49 For instance, owing to the lockdown imposed during the Covid-19 pandemic, university students had more discretionary time at their disposal, but their mental development was not yet adequately mature to develop autonomous habits. 50 They would manifest lower self-management skills in such an environment, 51 generating inertia in learning, which in turn leads to academic procrastination. 52 This finding is also confirmed in a study by Wang Shurui 53 which showed that university students' self-control negatively predicted academic procrastination.…”
Section: The Mediating Role Of Life Autonomymentioning
confidence: 99%